PSEUDOPOLIMORF GARAM SIPROFLOKSASIN DENGAN ASAM SALISILAT: KARAKTERISASI FASA PADAT, ANHIDRASI, DAN PENENTUAN KONSENTRASI SIMULTAN DENGAN KEMOMETRI - Tjengal, Billgerd
One problem that often arises during the formulation of a dosage form is the solubility and dissolution of the active ingredients. This problem arises in ciprofloxacin, a BCS class IV fluoroquinolone antibiotic. Pseudopolymorph is a kind of polymorph in which the number of hydrates is different. In this study, a new pseudopolymorph from ciprofloxacin and salicylic acid salt was found, namely its 1,75-hydrate form. This new solid phase was analyzed by FT-IR, Raman spectroscopy, and thermal analysis and proven by PXRD analysis. The 3D crystal lattice structure was successfully completed by SCXRD analysis and it’s unit cell parameters has been determined by refinement, it was found that the piperazinyl group of ciprofloxacin is protonated by H + from salicylic acid, and there was a water molecule that is in an inversion center between two ciprofloxacin molecules, which made its occupancy becomes 0,5. In addition, the hydrate was tried to be released using the grinding technique for 105 minutes, the hydrate loss from the new solid phase was then proved by analysis with FT-IR, Raman spectroscopy, thermal analysis and PXRD. UV-Vis spectrophotometry is used to determine the concentration of ciprofloxacin for the solubility and dissolution test. For the more accurate quantification of ciprofloxacin concentration in a mixture that contain salicylic acid, multiple linear regression chemometrics method was used. According to solubility and dissolution test, this new solid phase has a better profile than the original compound.